Spread of the slipper limpet Crepidula fornicata (L. 1758) in Europe. Current state and consequences - Blanchard, M. (Scientia Marina, 1997)
The present distribution of the slipper limpet Crepidula fornicata in Europe is described in detail for each country, and an overview provided thanks to new information. Main observations of introduction and spread, obtained from the literature, are discussed. For most of them, we observe that both aspects are due to oyster harvesting and farming. In the most heavily infested areas (France, England, the Netherlands), activities of dredging, harvesting and oyster farming have been disrupted. In France, these activities are so much hampered that treatment methods are now developed.